2016
DOI: 10.1117/12.2218363
|View full text |Cite
|
Sign up to set email alerts
|

Altered effective connectivity within default mode network in major depression disorder

Abstract: Understanding the neural basis of Major Depressive Disorder (MDD) is important for the diagnosis and treatment of this mental disorder. The default mode network (DMN) is considered to be highly involved in the MDD. To find directed interaction between DMN regions associated with the development of MDD, the effective connectivity within the DMN of the MDD patients and matched healthy controls was estimated by using a recently developed spectral dynamic causal modeling. Sixteen patients with MDD and sixteen matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(12 citation statements)
references
References 20 publications
2
10
0
Order By: Relevance
“…Firstly, results of review confirm previously literature about cerebral functional connectivity of MD patients compared to HC at baseline, generally presents dysfunction in the frontal-limbic circuit with cortical hypo-function and limbic hyperactivity (Davidson et al, 2002;Fitzgerald et al, 2008;Haldane and Frangou, 2006;Konarski et al, 2007;Mayberg, 2003;Murray et al, 2011;. Articles found decreased DLPFC recruitment, as well as, decrease in DLPFC connectivity with other structures in MD adults and TRD patients in resting-state Altinay et al, 2016;Li et al, 2016;Wei et al, 2014;, in adolescents in resting-state , in elderly patients in resting-state and during cognitive task processing . The authors also observed interhemispheric frontal structures connectivity decreased in MD adults (Abdallah et al, 2017).…”
Section: Discussion Of Baseline Key Findingssupporting
confidence: 74%
See 4 more Smart Citations
“…Firstly, results of review confirm previously literature about cerebral functional connectivity of MD patients compared to HC at baseline, generally presents dysfunction in the frontal-limbic circuit with cortical hypo-function and limbic hyperactivity (Davidson et al, 2002;Fitzgerald et al, 2008;Haldane and Frangou, 2006;Konarski et al, 2007;Mayberg, 2003;Murray et al, 2011;. Articles found decreased DLPFC recruitment, as well as, decrease in DLPFC connectivity with other structures in MD adults and TRD patients in resting-state Altinay et al, 2016;Li et al, 2016;Wei et al, 2014;, in adolescents in resting-state , in elderly patients in resting-state and during cognitive task processing . The authors also observed interhemispheric frontal structures connectivity decreased in MD adults (Abdallah et al, 2017).…”
Section: Discussion Of Baseline Key Findingssupporting
confidence: 74%
“…It was observed decrease in DMN connectivity in ten to sixteen articles (63%). Decrease of DMN/limbic structures connectivity by SSRI treatment to adolescents , in LLD elderly treated with SSRI or SNRI , TRD patients treated with ezogabine (Tan et al, 2018) and in MD first episode naïve adults treated with SSRI , as well as the decrease intrinsic DMN structures connectivity in adults and LLD elderly (Li et al, 2016;Li et al, 2017;Wang et al, 2014;Karim et al, 2017). In TRD adults the double dose psilocybin treatment increase in DMN structures connectivity (sgACC/PCC) in total patients post 5 weeks, but when there were analyzed separated this pattern was observed only in R-patients .…”
Section: Insert Table 1amentioning
confidence: 96%
See 3 more Smart Citations